2021
DOI: 10.1007/s11661-021-06334-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functionally Gradient Composites Al2O3-Cu-Mo Obtained via Centrifugal Slip Casting

Abstract: The investigations applied the original concept of the formation of materials as hybrid gradient composites. Two innovative technologies were used: formation by centrifugal slip casting and sintering with varying proportions of the liquid phase. This allowed us to create a gradient microstructure. This article presents the study of Al2O3-Cu-Mo gradient composites. This work aimed to determine the effect of the metallic phase content on the composite’s microstructure and basic properties. The most critical elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…FGMs are considered a new type of composite materials which exhibit a continuous change of properties along at least one direction due to the gradient distribution of their phases to achieve the needs of applications originating from industrial growth [1,[3][4][5]. Variations in chemical composition, size, morphology, and structure as a function of location influence the modification of functional and structural qualities [6][7][8][9]. As a result, FGMs outperformed and were more attractive than traditional composite materials.…”
Section: Functionally Graded Materials As New Promising Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…FGMs are considered a new type of composite materials which exhibit a continuous change of properties along at least one direction due to the gradient distribution of their phases to achieve the needs of applications originating from industrial growth [1,[3][4][5]. Variations in chemical composition, size, morphology, and structure as a function of location influence the modification of functional and structural qualities [6][7][8][9]. As a result, FGMs outperformed and were more attractive than traditional composite materials.…”
Section: Functionally Graded Materials As New Promising Materialsmentioning
confidence: 99%
“…FGMs are a novel type of heterogeneous composite materials defined by a continuous change of characteristics in at least one direction to achieve the demands of industrial applications [1,[3][4][5]. Variations in chemical composition, size, morphology, and structure as a function of location influence their functional and structural alterations [6][7][8][9]. They can either be a smooth gradient for homogeneous mixes or a sharp gradient for heterogeneous mixtures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the fabrication of composites that include copper as a metallic filler is still ongoing. The published research results showed that adding additional metallic components such as Cr, Mo, W, or Ni prevents leakage of liquid copper during sintering [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%